Perumusan Strategi Komunikasi Pemasaran Terpadu Pada Organisasi Dakwah - Mujianti, Fitri (INTELEKSIA: Jurnal Pengembangan Ilmu Dakwah, 2022)
Abstract: The concept of integrated marketing communication can be applied to da'wah organizations, although the concept arises from the problems experienced by most commercial companies and tends to be used in commercial marketing. Similar to profit organizations, da'wah organizations also carry out marketing communication efforts with the aim of changing people's behavior so that they carry out Islamic values. these goals are considered more difficult to achieve when compared to the purpose of purchasing goods or services. Conventional marketing strategies are considered less able to address these needs. This is due to the lack of synergy between the marketing communication mix. Integrated marketing communication is considered as a solution to this. This study aims to formulate an integrated marketing communication strategy in da'wah organizations. It is hoped that this research can be used as a guide for da'wah organizations in achieving marketing goals. This study uses a specific qualitative approach to adapt the theory of integrated marketing communication into a da'wah organization. The results of this study indicate that the goals and characteristics of the da'wah organization and Islamic aqidah ties are the main basis in the formulation of an integrated marketing communication strategy, this is reflected in the process of identifying the target audience to the process of forming the overall marketing communication mix. Keywords: strategy formulation, integrated marketing communication, da'wah organization